Quantitative cardiac magnetic resonance T2 imaging offers ability to non-invasively predict acute allograft rejection in children. (27th June 2020) - Sethi, Neeta; Doshi, Ashish; Doshi, Tina; Cross, Russell; Cronin, Ileen; Amin, Elena; Kanter, Joshua; Scheel, Janet; Khan, Sairah; Campbell-Washburn, Adrienne; Olivieri, Laura
Abstract: Background: Monitoring for acute allograft rejection improves outcomes after cardiac transplantation. Endomyocardial biopsy is the gold standard test defining rejection, but carries risk and has limitations. Cardiac magnetic resonance T2 mapping may be able to predict rejection in adults, but has not been studied in children. Our aim was to evaluate T2 mapping in identifying paediatric cardiac transplant patients with acute rejection. Methods: Eleven paediatric transplant patients presenting 18 times were prospectively enrolled for non-contrast cardiac magnetic resonance at 1.5 T followed by endomyocardial biopsy. Imaging included volumetry, flow, and T2 mapping. Regions of interest were manually selected on the T2 maps using the middle-third technique in the left ventricular septal and lateral wall in a short-axis and four-chamber slice. Mean and maximum T2 values were compared with Student's t-tests analysis. Results: Five cases of acute rejection were identified in three patients, including two cases of grade 2R on biopsy and three cases of negative biopsy treated for clinical symptoms attributed to rejection (new arrhythmia, decreased exercise capacity). A monotonic trend between increasing T2 values and higher biopsy grades was observed: grade 0R T2 53.4 ± 3 ms, grade 1R T2 54.5 ms ± 3 ms, grade 2R T2 61.3 ± 1 ms. The five rejection cases had significantly higher mean T2 values compared to cases without rejection (58.3 ± 4 ms versus 53 ± 2 ms, p = 0.001). Conclusions: Cardiac magnetic resonance with quantitative T2 mapping may offer a non-invasive method for screening paediatric cardiac transplant patients for acute allograft rejection. More data are needed to understand the relationship between T2 and rejection in children.